PUBLIC RELATIONS STRATEGY IN DEVELOPING WATER TOURISM IN SUNGGAL KANAN VILLAGE, SUNGGAL DISTRICT, DELI SERDANG REGENCY - Widianto, Arif; Alfikri, Muhammad (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
The purpose of this study is to find out how the application of public relations strategies in developing water tourism in â€œSunggal Kananâ€ village, Sunggal District, Deli Serdang Regency. This type of research is qualitative research using descriptive methods. In carrying out the research, the results were obtained that there is potential that can be developed by the indah dam water tourism manager together with the public relations of â€œSunggal Kananâ€ village. However, there are also obstacles that hinder the development and visitability of the community to the Indah dam water tourism. Efforts in developing water tourism in â€œSunggal Kananâ€ village that can be done by public relations are by analyzing and making a strategy in managing the management of the Indah dam water tourism which is under the auspices of BUMDes or â€œSunggal Kananâ€ Village Owned Business Entity.Â  This is the main capital in the development of tourism in the village of â€œSunggal Kananâ€. Therefore, in this research, a PUBLIC RELATIONS strategy will be designed to develop tourism in â€œSunggal Kananâ€ village using a SWOT analysis.